The Role of International Research in Teaching Natural Sciences in Primary Grades - G’aniyeva Gulhayo Islom qizi (Researchparks Publishing, 2023)
Today, the need to implement large-scale reforms in the field of improving natural science teaching on the basis of multimedia tools, international assessment programs and improving the natural-scientific literacy of students in the classroom is growing. In the UN agreement on education, science and culture